Analysis on the Financial Performance of Selected Cement Industries of Bangladesh - Ershad, Subarna; Uddin, Md. Minhaz; Faruk, Md. Omar (International Journal of Finance Research, 2021)
This paper aims to analyze the financial performance of industries of Bangladesh, which are performing a crucial role in the current economic development trend of the country. Heidelberg Cement Bangladesh Ltd, Crown Cement, Lafarge Holcim and Meghna Cements are selected for analysis for their 70% of market share coverage of the cement industry. Competency of selected leading four cement companies are looked over here with some financial parameters like Return on Asset (ROA), Return on Equity (ROE), Earnings Per Share (EPS), Total Debt Ratio (TDR), Current Ratio (CR), Net Working Capital Ratio (NWCR), Assets Turnover Ratio (ATR) and mean value analysis technique. In preferred financial parameters and mean value analysis technique Heidelberg Cement Bangladesh Ltd has a good position, and in most cases, Meghna Cements obtained the lowest score. To attain desired efficacy in the cement industry of Bangladesh shortly, some prime recommendations such as reduction of production cost, prioritization on economies of scale, and business augmentation have come up here.